Mapeamento de processos aplicado na comercialização de usinas solares fotovoltaicas na cidade de Mossoró-RN - Silva, Luiz Joaquim Diniz da (Universidade Federal Rural do Semi-Árido, 2019)
Process management enables organizations to reshape their service systems to achieve improvements in their results, using organizational resources efficiently and enabling improvement in the value delivered to the client. Thus, the present study has the general objective of mapping the business processes related to the commercialization of solar photovoltaic plants in a small company operating in the city of Mossoró-RN and, through this, to propose improvements in the management of commercialization through redesign and documentation of their processes. To that end, a methodology of applied research was adopted through a qualitative-quantitative approach and, as a sketch of the research, the case study was chosen. The company analyzed is a company in the field of engineering, which provides services in the field of civil and electrical engineering, in the area of electrical engineering stands out the commercialization of solar photovoltaic plants (routine is chosen to carry out the study). In the results, it is presented all the phases used to perform the mapping, critical analysis and suggestions for improvement and, finally, the redesign of the analyzed process as necessary. It is understood, conclusively, that the study allows for improvements in the interrelation between those involved in the process, better dynamization in communication and distribution of information and standardization, reflecting in the reduction of the process and, consequently, generating greater customer satisfaction.
Monografia
Keywords: Gestão por processos; Empresa de pequeno porte; Comercialização; Mapeamento de processos; Process management; Short business; Commercialization; Mapping methods; ENGENHARIAS::ENGENHARIA DE PRODUCAO